Chemometrics assisted uv visible spectrophotometric method for simultaneous estimation of four components from herbal formulations (Funded work) - K.LAKSHMI; G.NEELIMA; D.BALANAGAMANI (International Journal of Pharma and Bio Sciences, 2019)
A simple, rapid and robust method are reported for the simultaneous analysis of ternary components Ascorbic acid (ACA), Gallic Acid (GAA), Embelin (EMB) and Piperine (PIP) from herbal formulations. Spectra of all the four components revealed an absolute overlap and these reported methods could overcome the spectral interference. These methods are based on the use of spectrophotometric data coupled with Partial Least Squares (PLS) and Principal Component Regression (PCR). The Spectra of all four drugs were recorded at concentrations within the linear range of 0-3 µg/mL of ACA and EMB, 0-6 µg/mL of GAA and 0-5-2.5 µg/mL of PIP respectively. These spectra were used to compute a total of 35 synthetic mixtures comprising of 25 calibration and 10 validation sets between the wavelength range of 200 – 350 nm with the wavelength interval of 1 nm in hydroalcoholic solution (water: methanol in the ratio of 1:1).The root mean squareerror (RMSE) values of calibration and prediction sets were used to assess the suitability of the method. The analytical performance of the reported methods was by means of percentage recovery data. These methods were successfully applied to ayurvedic formulations and the drugs were evaluated without any interference from other compounds. These methods provide rapid analysis and could be employed for routine quality control.